Introduction to Aramean and Syriac Studies : a manual - Akopian, Arman (Gorgias handbooks., 2017)
Originally published in Armeanian, this comprehensive introduction to Aramean and Syriac studies provides a gateway to the history, language, culture, and religion of the Aramean/Syriac people from ancient times, through to the modern day. Special attention is given to such topics as translation and literary activity of the Syriacs, their missionary zeal and role as an intercultural medium, denominational fragmentation, and identity issues. The book is intended for the students of Oriental and Semitic studies but will be of value to anyone interested in the history and culture heritage of the Christian Orient--Publisher.